Coverage of scientific publishers in Book citation index in social sciences and humanities: is history repeating itself? - Torres-Salinas, Daniel; Delgado-López-Cózas, Emilio (Anuario ThinkEPI, 2013)
In 2010 Thomson launched a new citation index devoted to books: the Book citation index. This new database has opened new possibilities for analyzing fields such as the Humanities and Social Sciences from a bibliometric point of view. However we still know little about their coverage and especially about the scientific publishers that have been taken into account in the construction of this citation database. In this paper we analyze the BKCI coverage: countries, languages, concentration of publishers and finally we compare the database with Scholarly publishers indicators (SPI), produced in Spain by CCHS/CSIC. The conclusion is that Thomson is making the same mistakes as before: a clear Anglo-Saxon bias, a large concentration of publishers and an absence of a number of reputable publishers.